Effectiveness of Social Studies Learning in Elementary School Using Strategy of Everyone is a Teacher Here (EiTH) - Suparno, Suparno; Iasha, Vina (Opción, 2019)
This study aims to examine the effectiveness of the learning strategy of every- one is a teacher here (EiTH) in increasing the learning activities of elementary students in social studies learning. In more detail, this article will reveal what types of learning activities increase when students are given learning using EiTH strategies. The research used quasi-experimental method. This study involved two classes of fifth-grade students of SD Negeri Ciruas 4, Serang City, Banten Province, with a total of 30, respectively. The results showed that out of 10 student activities observed during learning, 4 student activities im- proved well when using EiTH learning strategies, namely: asking questions, expressing opinions, actively participating in group discussions, and conclud- ing the learning that had been done. This strengthens the recommendation that to improve student learning activities, EiTH learning strategies were considered effective.